Antilisterial activity of lactic acid bacteria isolated from "Alheiras" (traditional Portuguese fermented sausages) - Albano, Helena (2010)
A total of 226 lactic acid bacteria (LAB) isolated from ‘‘Alheira’’, a traditional Portuguese fermented sausage, were screened for antagonistic activity against some pathogenic microorganisms, including Listeria monocytogenes. The objective was to isolate LAB with antibacterial activity from ‘‘Alheiras’’ and to select strains that could be used in ‘‘Alheira’’ production. Isolates displaying antibacterial activity against Listeria innocua and L. monocytogenes were investigated for the nature of the antibacterial compounds active against these microorganisms. Results showed that two LAB cultures retained activity in the supernatants after neutralization and catalase treatment. These two strains were both identified as Pediococcus pentosaceus. The final aim of this work was to test the antilisterial activity of these two strains during storage of ‘‘Alheira mass’’ (sterilized), at 4 C. The growth of L. innocua population was significantly suppressed in the paste of ‘‘Alheira’’ when the samples were co-inoculated with the LAB strains, in comparison with the paste only inoculated with L. innocua or co-inoculated with a bacteriocin negative strain of Ped. pentosaceus (ca. 1 · 107 CFU/g after 28 days of incubation).